Forms of relation : composing kinship in colonial Spanish America - Goldmark, Matthew, 1985- (Writing the early Americas., 2023)
"The book argues that colonial administrative texts not only documented but also helped to produce kinship ties in the sixteenth- and seventeenth-century Spanish Americas"--